Optimizing Educational Quality in Private Madrasahs: The Influence of Human Resource Management, Organizational Culture, and Community Participation in Pekanbaru City - Darimus Darimus; M. Daffa Hanif (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine the effect of human resource management, organizational culture, and community participation on the quality of education. This research was conducted in private Madrasas throughout Pekanbaru City. This research is a quantitative research using a causal method, a path analysis technique approach. Respondents to this study were the heads of Madrasahs, Educators and Education Personnel, Madrasah Superintendents, Heads of Madrasah Sections and Madrasah Committees who were selected based on simple random sampling. The research findings are: first, there is a positive direct effect of human resource management on the quality of education, secondly, there is a positive direct effect of organizational culture on the quality of education, thirdly, there is a positive direct effect of community participation on the quality of education, fourthly, there is a positive direct effect of management human resources on community participation, fifth, there is influence positive direct organizational culture on community participation and Sixth, there is a significant influence of human resource management on organizational culture. Based on these findings, it can be concluded that the quality of education is influenced simultaneously and partially by human resource management, organizational culture, and community participation. Meanwhile, community participation is significantly influenced by human resource management and organizational culture. Meanwhile, organizational culture is significantly influenced by human resource management. The implication of this research is that efforts to improve the quality of education can be carried out through the application of human resource management, organizational culture and community participation.